Disrupting Advertising Models: How Social Media are used as New Business Frontiers among Student Entrepreneurs in some Universities in South-South Nigeria - ODOEMELAM, CHINEDU CHRISTIAN (Journal of Central and Eastern European African Studies, 2024)
Social media provide platforms for small businesses that neither have the funds nor can compete favourably for advertisement space and time with large-scale businesses to create awareness for their goods and services. Based on the premise that social media has potentials to create visibility for small businesses, this study examined whether students who engage in small businesses know that advertising can help their businesses grow; and how they use social media to advertise their goods and services. These issues were interrogated within the context of the uses and gratification and domestication of technology theories. Data came from a cross-sectional survey of 193 subset of the population that were rando mly selected from two universities across two States in the south-southern Nigeria through multi-stage sampling techniques. One Hundred and Eighty respondents were included in the final sample (n=180). Respondents were (n=101, 56.1%; Males, n=79, 43.9%) participants. Findings suggest that social media platforms foster economic development and define new frontiers for small businesses among student entrepreneurs. They study bears implications for curriculum on entrepreneurship in Nigerian universities to leverage on the potentials of social media in promoting advertising among Nigerian students.